NILAI – NILAI PENDIDIKAN AHLUSSUNNAH WAL JAMA’AH AN NAHDLIYYAH UNTUK MEMBENTUK KARAKTER RAHMATAN LIL ‘ALAMIN SANTRI PONDOK PESANTREN DARUL HIKMAH BALEN BOJONEGORO - Burhanuddin, Hamam; Sulistyowati, Titin (International Conference on Humanity Education and Society (ICHES), 2024)
Basically Islam carries the teachings of rahmatan lil’alamin(compassion for all nature). However, the reality is that inter-religious harmony in Indonesia is still being debated. The cause of the controversy is the growth and development of thoughts and movements of radical Islamic groups. Responding to the growth and development of radical understanding movements, Islamic organizations in Indonesia need to respond actively, creatively, constructively and solutively in counteracting this radical understanding. One of the religious organizations that is active in countering radicalism is Ahlussunnah Wal Jama'ah An Nahdliyyah. Based on this description, the researcher is interested in writing a thesis entitled Education Values of Ahlussunnah Wal Jama'ah An Nahdliyyah to Shape the Character of Santri Rahmatan Lil 'Alamin Darul Hikmah Balen Bojonegoro Islamic Boarding School. This study aims to describe and analyze what are the educational values of Ahlussunnah Wal Jama'ah An Nahdliyyah, what are the forms of implementation and what are the factors that support and hinder this implementation. This type of research is a qualitative description. Sources of research data are caregivers, coaches, and students, as well as documentation of Darul Hikmah Balen Bojonegoro Islamic Boarding School. The results of the research findings, namely the educational values of Ahlussunnah Wal Jama'ah An Nahdliyyah have reached the target to shape the character of the students Rahmatan Lil 'Alamin at the Darul Hikmah Balen Bojonegoro Islamic Boarding School by always applying the principles of Ahlussunnah Wal Jama'ah An Nahdliyyah values. Implementation is carried out by providing students with the basics of the Ahlussunnah Wal Jama'ah An Nahdliyyah practice. In addition, the practice of amaliyah - amaliyah which contains educational values Ahlussunnah Wal Jama'ah An Nahdliyyah such as reciting the yellow book, yasinan, tahlilan, istighosah, reading manaqib, reading sholawat, reading rotib, and bahtsul masa'il. The supporting factors are the students' awareness and enthusiasm for reciting the Koran, motivation from parents, siblings, clerics and supervisors. While the inhibiting factors include the negative influence of friends, laziness, low vocabulary of students, low knowledge of the basics of Ahlussunnah Wal Jama'ah An Nahdliyyah amaliyah.